Consent: Practical Principles For Clinicians - C. McILwain, Jeffrey (Bentham Science Publishers, 2011)
Obtaining proper patient consent in clinical care is vital in current times. The approach of 'doctor knows best' is now superseded by patient rights to make decisions. The approach of this book from the author's experience of 13 years in Clinical Risk Management with a special interest in generic consent is to combine different disciplines into a more unified approach that reflects every day practice, rather than citing individual examples of law case studies. By analyzing the elements of these different disciplines a more logical, practical and synergistic approach to consent is achieved. This book differs from others in that the principle elements are combined into one text. The book should help professional and trainee clinicians to acquire a wider understanding of the fundamental principles of medical law, ethics and risk management and their combined role in many situations, particularly in the NHS.